A griffith crack in coated-fiber reinforced composite materials - Chen, Cheng (2016)
This project covers the parameter study of the stress intensity factors and CTOD of cracks in composite materials, to simulate and study the propagation of crack by changing size and properties of fiber-reinforced material. The analysis of crack in composites is performed by Abaqus CAE, which is powerful computer aided engineering simulation software. It is executed to model a 2-diamensional composite part with a horizontal crack in the central portion and inclusion with different material properties. The stress intensity factor of the crack, K1 which is the stress intensity factor in mode 1 in modes of fracture mechanics, is recorded. The ratios of stress intensity factor from experiments and theory were plotted for analysis. Different distances between crack and inclusion, size of inclusion and different Young’s modulus of materials are studied. The experiment has shown that stress intensity factor approaches to the theoretical value when the distance between crack and inclusion increases. When the size of inclusion increases, the stress intensity factor decreases for those specimens whose ratio of Young’s modulus greater than 1.Stress intensity factor increases for those specimens whose Young’s ratio of modulus less than 1. A separate analysis is executed to study the behavior of the stress intensity factor and CTOD at the tips of crack, when the inclusion is coated by coating material with variable thickness and Young’s modulus. It shows that the stress intensity factor increases when coating material’s thickness increases, ratio of Young’s modulus between coating material and inclusion is less than 1. Stress intensity factor decreases as thickness increases, when the ratio is greater than 1. The variation of CTOD (crack tip opening displacement) comes out similar results on stiffness of composite material, as what stress intensity factor shows with the same setting parameters. When stress intensity factor and CTOD decrease, material is stiffer to resist the propagation of crack. And material becomes harder to prevent the propagation of crack when stress intensity factor and CTOD increase.